Prototype WSN platform for performing dynamic monitoring of civil engineering structures - Aguilar, Rafael (2011)
Structural Health Monitoring represents the present and future of the civil engineering since, until few years ago, structural diagnosis works had been performed with few resources regarding to experimental techniques. Precisely in the field of monitoring sensors, the progress of new technologies based on wireless communications and Micro-Electro-Mechanical- Systems (MEMS) are of high interest for replacing the handle difficult wired sensors. However, three major limitations of the commercial off-the-shelf technology on WSN (combination of MEMS and wireless technology) for performing dynamic monitoring were identified by means of: (1) not enough sensitivity of the accelerometers; (2) low resolution of the ADC embedded; and (3) lack of synchronization algorithms implemented. This paper presents a new prototype system conceived for performing dynamic monitoring civil engineering structures. This system was jointly conceived by a team of civil, electrical and communication engineers and is a combination of the last technology on high resolution MEMS accelerometers and the state of the art of communication technologies. Despite the fact that the prototype system needs more improvements; the results of several rounds of validation experiences confirm the feasibility for its consideration as an alternative to the conventional wired based sensors.